Modelo de risco e decisão de crédito baseado em estrutura de capital com informação assimétrica - Dantas, Régis Façanha (2006)
This work to research the theory about enterprises financial, financial struture, risk of the borrower(enterprises) to repay the loan, credit of banks. In views of the optimal capital struture, credit analyses examines factors that may lead to default in the repayment of a loan. As for the risk management the general kinds of risks are described, particularly the credit risc and the credit concession models are evaluated. The risc models will have the financial demonstrations of interprises, here can be viewed as a signal, about the concept of asymmetric information. Thus, the signal to leave a nash equilibrium in this credit market. In the development of the statistic model, using the Logit Model because the problems of functional form of the linear probability model, the resíduos is heteroscedastic and not have normal distribuition. The discriminant analyse, probit e logit will be test. Another important point in this work is the decision model. This model have predtion of interest to improve the decision with the cutoff. Referring to the factorial analyse in the statistic of the independentes variable, the use of factorial analyses is not observations in the reference. Having this purpose in mind a statistic model was developed, using logit regression with factorial analyse in variable and linear programming. This project aims at evaluating the used models and proposing the adoption of new models, for the allowance for dobtful accounts, with the objetive of mensuring the risk related to customers financing and loan activities.